2015
DOI: 10.3892/mmr.2015.3159
|View full text |Cite
|
Sign up to set email alerts
|

Identification of suitable reference genes for gene expression studies using quantitative polymerase chain reaction in lung cancer in vitro

Abstract: The present study aimed to examine 10 housekeeping genes (HKGs), including 18s ribosomal RNA (18S), glyceraldehyde‑3‑phosphate dehydrogenase (GAPDH), ribosomal protein large P0 (RPLP0), β‑actin (ACTB), peptidylprolyl isomerase A (PPIA), phosphoglycerate kinase‑1 (PGK1), β‑2‑microglobulin (B2M), ribosomal protein LI3a (RPL13A), hypoxanthine phosphoribosyl transferase‑1 (HPRT1) and TATA box binding protein (TBP) in order to identify the most stable and suitable reference genes for use in expression studies in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 37 publications
5
35
0
Order By: Relevance
“…RPLP0 has been claimed a suitable reference for human intestinal epithelial cells (Dydensborg et al 2006). In turn, PPIA has been repeatedly found a suitable normalizer in a number of human studies (Andrusiewicz et al 2016; Ali et al 2015; Lemma et al 2016), also these concerning CRC patients (Sørby et al 2010; Kheirelseid et al 2010), but affected by cell stimulation in others (Kaszubowska et al 2015). IPO8 and GUSB were yet another HKG recommended for CRC studies (Sørby et al 2010; Blanquicett et al 2002) and highly ranked in our in vitro study as well.…”
Section: Discussionmentioning
confidence: 99%
“…RPLP0 has been claimed a suitable reference for human intestinal epithelial cells (Dydensborg et al 2006). In turn, PPIA has been repeatedly found a suitable normalizer in a number of human studies (Andrusiewicz et al 2016; Ali et al 2015; Lemma et al 2016), also these concerning CRC patients (Sørby et al 2010; Kheirelseid et al 2010), but affected by cell stimulation in others (Kaszubowska et al 2015). IPO8 and GUSB were yet another HKG recommended for CRC studies (Sørby et al 2010; Blanquicett et al 2002) and highly ranked in our in vitro study as well.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of this technique is criticallydependent on good normalization: even with identical starting material, slight differences in the efficiency of RNA isolation or cDNA synthesis can significantly affect subsequent quantitation. Effective normalization requires appropriate reference genes, and indeed efforts to identify, validate and publicize such genes are becoming more common in a variety of disease states [20][21][22][23][24] and model organisms [25][26][27][28][29][30]. A review of the literature specifically within the DMD field however reveals a considerable number of candidates: selected examples in dystrophic dogs include GAPDH [31][32][33], RPS18 [34], HPRT1 [35,36], 18S [37]; in humans, TBP and GUSB [13]; and in mice GAPDH [33,38], ActB [39], 18S [40].…”
Section: Introductionmentioning
confidence: 99%
“…In general, internal reference genes, such as 18S rRNA, GAPDH, and ACTB, are chosen for relative quantification analysis between clinical samples. However, increasing evidence has suggested that the expression levels of these commonly used internal reference genes are variable in distinct tissues, cell lines, between treatments of the same cell line (Ali et al, 2015; Ma et al, 2015; Yang et al, 2014; Yu et al, 2015), as well as across cell types (He et al, 2015; Li et al, 2015a; Li et al, 2015b). Thus, with the advancement of precise medicine, it is of high importance to evaluate and validate internal reference genes for the target gene expression profile studies among different cell types and tissues.…”
Section: Introductionmentioning
confidence: 99%